Karakteristik Fruit Leather Buah Pepaya (Carica papaya L.) dan Buah Nanas (Ananas comosus L.) dengan Proporsi Konsentrasi Gum Arab dan Asam Sitrat - Luthfiana Adzani Zulfa; Devi Dwi Siskawardani; Dahlia Elianarni (Universitas Muhammadiyah Malang, 2026)
Fruit leather processed was used as a fruit preservation process. The characteristics of fruit leather that are suitable if easy to roll and had fruit flavor consistency. Determination of hydrocolloids and acid compounds was important on the formation of fruit leather according to the characteristics. The purpose of this study was to determine the interaction of the addition concentrations of gum arabic and citric acid on the physicochemical characteristics of papaya pineapple fruit leather. The method used was a factorial Randomized Block Design (RBD. The first treatment was the concentrations gum arabic A (1%; 3%; 5%) and the second treatment was the concentrations citric acid B (0.2%; 0.4%; 0.6%). The addition of gum arabic and citric acid concentrations interacted significantly on the texture analysis and very significantly interacted on the organoleptic taste, color, texture, and preference of papaya pineapple fruit leather. The best treatment was A1B2 (1% gum arabic and 0.4% citric acid), resulted on the texture was 19.89 N; color intensity (L * 40.95 a * 3.84 b * 4.00); water content 10.16%; vitamin C 10.23 mg/100g; crude fiber 2.85%; pH level 3.41; and organoleptic taste 3.00 (neutral), aroma 2.91 (pineapple aroma), color 3.48 (yellow-orange), texture 3.48 (soft), preference 3.78 (rather like).